A compact implementation of a negative switched-capacitor voltage regulator dedicated to body-biasing of CMOS circuits. (February 2017) - Souvignet, Thomas; Allard, Bruno; Mas, Alexandre
Abstract: A fully integrated negative voltage regulator dedicated to body-biased circuits in FDSOI is proposed and validated through simulation. The regulator comprises an original negative switched-capacitor converter with a frequency modulation control loop. It can be digitally programmed by step of 100 mV in 100 μs time-scale from 100 mV to 1.3 V of negative voltage. The maximum overall power consumption is 20 μA to drive 1 mm 2 of digital load. Abstract : Highlights: Fully depleted Silicon-On-Insulator technology offers the option of back-biasing. Back-biasing improves transistors' performances. A converter is required to generate a negative voltage from the top positive voltage. A switch-mode converter is required for the sake of efficiency. An original switched-capacitor topology is verified through simulation.